Terminologie militante et changement social : le cas du terme femicide dans le discours de l’ONU sur la violence envers les femmes - Célia Atzeni (Anglophonia)
Starting from the more general aim of studying the way in which language choices might influence and reflect social change on the issue of violence against women, this article looks at the use of the term “femicide” in a diachronic computerised corpus that is made up of reports and press releases published by the UN between 1996 and 2019. We observed the predominance of the term “femicide” compared to other terms designating acts of violence resulting in the death of one or several women, with a significant increase in its use in the 2010’s. The reasons for such a predominance are investigated from a socio-historical perspective, within the framework of critical discourse analysis. We argue that the use of the term femicide in the UN’s discourse has had a mixed impact with regard to the social changes that it was supposed to bring about.